Formulation and in-vitro evaluation of Propranolol Hcl mucoadhesive vaginal beads for contraceptive purposes. - Eman Gomaa; Mennatullah M. Faisal (Zagazig Journal of Pharmaceutical Sciences, 2023)
Purpose: Based on the clinical findings on the efficacy of propranolol Hcl as a potent spermicide, the present study was designed to develop new sustained-release intravaginal propranolol-HCl-loaded alginate beads for contraceptive purposes. Method: Mucoadhesive vaginal beads were developed using an ionotropic gelation method with different ratios of the mucoadhesive polymer (Na alginate) to the cross-linking agent (calcium chloride). The prepared beads were examined and evaluated for their particle size, pH, entrapment efficiency % and their yield percentage, in-vitro bioadhesion, percentage of swelling and tested for stability.